초심상담자의 부적응적 완벽주의와 자기몰입이 심리적 소진에 미치는 영향: 무조건적 자기수용의 조절된 매개효과 - 송주미; Song Ju Mi; 최가희; Choi Gahee (인간이해, 2024)
본 연구의 목적은 초심상담자의 부적응적 완벽주의가 자기몰입을 통해 심리적 소진에 미치는 영향을 무조건적 자기수용이 조절하는지 검증하는 것이다. 전국의 경력 3년 이하의 초심상담자 251명이 부적응적 완벽주의 척도, 심리적 소진 척도, 자기몰입 척도, 무조건적 자기수용 척도, 인구통계학적 질문지를 포함한 온라인 설문조사에 응답하였다. 본 연구의 결과는 다음과 같다. 첫째, 자기몰입은 초심상담자의 부적응적 완벽주의와 심리적 소진의 관계를 부분매개하는 것으로 나타났다. 둘째, 무조건적 자기수용의 하위요인 중 판단분별로부터 자기수용이 자기몰입과 심리적 소진의 관계를 조절하는 것으로 나타났다. 셋째, 판단분별로부터 자기수용은 초심상담자의 부적응적 완벽주의와 심리적 소진의 관계에서 자기몰입의 매개효과를 조절하는 것으로 나타났다. 본 연구는 초심상담자의 부적응적 완벽주의가 심리적 소진에 이르는 과정에서 자기몰입이 중요한 심리적 기제임을 보여주었으며, 상담자의 판단분별로부터 자기수용의 수준이 높을수록 자기몰입의 부정적인 영향이 완화됨을 보여주었다. 이러한 결과는 초심상담자가 자신을 수용하고 자신의 유능성보다는 내담자와의 상담과정에 집중하도록 돕는 것이 상담자 소진을 방지할 수 있는 중요한 요인임을 시사하는 것이다. This study examined to examine the moderated mediating effect of unconditional self-acceptance on the relationship among novice counselor’s maladaptive perfectionism, self-absorption and psychological burnout. A total of 251 novice counselors nationwide responded to an online survey. The results of the study are as follows. First, self-absorption partially mediated the relationship between novice counselor’s maladaptive perfectionism and psychological burnout. Second, self-acceptance from judgment discrimination, one of sub-factors of unconditional self-acceptance, moderated the relationship between self-absorption and psychological burnout. also Self-acceptance from judgment discrimination moderated the mediating effect of self-absorption on the relationship novice counselor’s maladaptive perfectionism and psychological burnout. The result showed that the negative effect of self-absorption can be mitigated by increased level of unconditional self-acceptance.